L-band scintillation and TEC variations on St. Patrick's Day storm of 17 March 2015 over Indian longitudes using GPS and GLONASS observations - Srinivasu, V. K. D.; Prasad, D. S. V. V. D.; Niranjan, K.; Seemala, Gopi K.; Venkatesh, K. (My University, 2019)
The aim of the present study is to investigate the response of ionospheric total electron content (TEC), Global Positioning System (GPS) and Global Navigation Satellite System (GLONASS) scintillations during 17 March 2015 St. Patrick’s Day geomagnetic storm over Visakhapatnam, which is popularly known as Waltair (WALT) in the literature. GPS TEC observations obtained from five IGS stations (SGOC, IISC, HYDE, LCK4 and LHAZ) and WALT during the storm have been compared. The TEC derived from GPS, GLONASS constellations and CODE global ionosphere TEC map (GIM) over WALT has also been compared. Positive storm effect during the main phase of the storm and negative storm effect during the recovery phase of the storm were observed over the said stations. The variation of northern equatorial ionisation anomaly TEC (CODE GIM TEC maps) in response to the St. Patrick’s Day storm over four Indian longitudes (75◦E, 80◦E, 85◦E and 90◦E) has also been presented. Strong amplitude and phase scintillations were observed in the L-band signals of GPS and GLONASS constellations over WALT. Twelve satellite (Pseudo Random Noise) PRNs of GPS L1 and nine PRNs of each GLONASS L1 and L2-band signals were affected by strong amplitude and phase scintillation. The peak amplitude scintillation index (S4) obtained from the effected PRNs of GPS L1 signal and GLONASS L1-band signals over WALT range from 0.36 to 0.74 and 0.36 to 0.76, respectively. Strong fluctuations in rate of TEC index are noted over the said stations. This enhanced scintillation activity is mainly due to the main phase of the storm falls in the evening sector over the Indian region.
Keywords: GPS; Magnetic storm; GLONASS; L-band scintillations; ROTI